MODERASI BERAGAMA DALAM PERSPEKTIF EKOLOGI: TELAAH KONSEPTUAL TENTANG TANGGUNG JAWAB LINGKUNGAN DALAM ISLAM - Fina Amaliyatus Sholihah; Muhammad Najib (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The global environmental crisis indicates that ecological issues are rooted in the ethical and spiritual crises of modern humans. This article aims to conceptually examine the relationship between religious moderation and environmental responsibility within an Islamic perspective. Using a qualitative approach based on a literature review and content analysis, the study finds that religious moderation possesses an ecological dimension derived from the principles of wasathiyyah, tawāzun, and cosmic justice. The concepts of tawhid, khalifah, amanah, and the prohibition of israf form a normative framework that positions humans as responsible managers of the Earth. Thus, religious moderation serves as an Islamic ecological ethical paradigm relevant to responding to contemporary environmental crises